Security Uncertainty and Reorganization of Urban Spaces in the City of Ouagadougou - Bacyé, Yisso Fidèle; Zangré, Konseiga Kisswendsida Romaine; Kabore, Windlanaba Etienne (Advances in Social Sciences Research Journal, 2023)
The security crisis that Burkina Faso is experiencing, although mainly occurring in rural areas, is influencing the behavior of citizens in terms of urban infrastructure development. In fact, public area in the city of Ouagadougou is constantly being redesigned to take into account the uncertainty of a terrorist attack. Military and paramilitary spaces are equipped with security devices² forcing road users to bypass them to access services. What explains the choice of barriers requiring the disorganization of urban space? The objective of this research is to understand the determinants of the choice of the layout of barriers in lieu of the adoption of innovative means of surveillance and to identify the process of establishing these barriers. The research method is qualitative and is operationalized through in-depth interviews with a variety of people, including municipal services, security services, and users of services adjacent to the security services. The results show a lack of coordination between the municipal services in charge of urban planning and the security services that adopt road closures. A low use of digital surveillance equipment and a weak capacity to react in case of danger explain the choice of the use of protective barriers and barbed wire.